First detection of bovine viral diarrhea virus using antigen capture ELISA and RT-PCR assay in cattle with respiratory and abortive issues in Morocco (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: This research assessed the prevalence of Bovine Viral Diarrhea Virus (BVDV) among cattle herds from five provinces in the Casablanca-Settat region of Morocco (Benslimane, Settat, Berrechid, El Jadida, and Sidi Bennour), which experience respiratory and reproductive disorders. Antigen capture ELISA and real-time RT-PCR were utilized for the detection of BVDV. Materials and Methods: From January 2021 to June 2025, 500 blood serum samples and 500 leukocyte samples from cattle with respiratory or abortive symptoms were collected and analyzed using an antigen capture ELISA assay and a real-time RT-PCR assay, respectively, for BVD antigens or genome sequence. Results: Of the 500 sampled cattle, 9 (1.8%) tested positive, with all 9 results being actively infected with BVDV confirmed via RT-PCR test. The positive results were found across four provinces; Benslimane had the highest proportion of positive cases (44.4%), while Settat and Berrechid each had 22.2% of the positives, and El Jadida had one (11.1%) case. No cases were found in Sidi Bennour. Conclusion: This study presents the first documented case of bovine viral diarrhea virus infection in Morocco, highlighting its potential for widespread circulation in the country. These results underscore the need for further studies to isolate and characterize circulating strains of BVDV, with the goal of developing effective prevention and control strategies to minimize their negative impacts on cattle health and productivity.J. Adv. Vet. Anim. Res., 12(4): 1243–1249, December 2025http://doi.org/10.5455/javar.2025.l985